1991
DOI: 10.1007/bf00243718
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging reflects cartilage proteoglycan degradation in the rabbit knee

Abstract: Cartilage degeneration in osteoarthritis is initiated by a loss of proteoglycan. Intra-articular injection of papain causes a reversible loss of proteoglycan in rabbit knees. Rabbits were scanned with magnetic resonance imaging (MRI), using a 1.5T Signa superconducting magnet with 3 inch surface coil. Spin echo sequences were performed in the coronal and sagittal planes at 0, 24, 48, and 72 h after intra-articular injection of papain to obtain T1, proton density, and T2-weighted images. Cartilage proteoglycan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 21 publications
5
28
1
Order By: Relevance
“…2E versus 2A) was only slightly diminished compared with the untreated knee (87 2 7%; n = 6). This result is in accordance with findings that the removal of PG from the cartilage does not significantly alter its MRI properties [TI, T,, and proton density) (7). MR images of the papain-treated knees revealed no surface irregularities or focal defects of the cartilage.…”
Section: Resultssupporting
confidence: 94%
“…2E versus 2A) was only slightly diminished compared with the untreated knee (87 2 7%; n = 6). This result is in accordance with findings that the removal of PG from the cartilage does not significantly alter its MRI properties [TI, T,, and proton density) (7). MR images of the papain-treated knees revealed no surface irregularities or focal defects of the cartilage.…”
Section: Resultssupporting
confidence: 94%
“…Although some studies show that MRI assessment of the vascularity of the proximal scaphoid does not predict whether a fracture will unite after conservative treatment [31], MRI is still considered the most reliable test for the pre-operative diagnosis of avascular necrosis and is the test used most frequently in this setting [19,32]. According to Donati et al [33], MRI without contrast better diagnosed avascular necrosis of the proximal segment of the scaphoid compared to MRI with gadolinium contrast, and tests without contrast were simpler and safer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al [36] in their pioneer in vivo study on rabbit knees obtained T1-, PDand T2-weighted images at 312-µm resolution after intra-articular injection of papain. They found that reduced articular cartilage thickness on the MR images of papain-treated knees corresponded to changes in cartilage proteoglycan content.…”
Section: Pathomimetic Studies and Contrast Agentsmentioning
confidence: 99%